Effects of root addition and foliar application of nitric oxide and salicylic acid in alleviating iron deficiency induced chlorosis of peanut seedlings. (2nd January 2017) - Song, Yiling; Dong, Yuanjie; Kong, Jing; Tian, Xianyi; Bai, Xiaoying; Xu, Linlin
ABSTRACT: Nitric oxide (NO) and salicylic acid (SA) are two important signaling molecules, which could alleviate chlorosis of peanut under iron (Fe) deficiency. Here, we further investigated the mechanism of different combinations of sodium nitroprusside (SNP, a nitric oxide donor) and SA supplying in alleviation Fe deficiency symptoms and selected which is the best combination. Thus, peanut was cultivated in hydroponic culture under iron limiting condition with different combinations of SNP and SA application. After 21 days, Fe deficiency significantly inhibited peanut growth, decreased soluble Fe concentration and chlorophyll contents, and disturbed ionic homeostasis. In addition, the content of reactive oxygen species (ROS) and malondialdehyde (MDA) concentration increased, which led the lipid peroxidation. Application of SNP and SA significantly changed Fe trafficking in cells and organs, which increased Fe uptake from nutrient solution, and transport from root to shoot, enhanced the activity of ferric-chelate reductase (FCR), that increased the available Fe in cell organelles, and the active Fe, chlorophyll contents in leaves. Furthermore, ameliorated the inhibition of calcium (Ca), magnesium (Mg) and zinc (Zn) uptake and promoted plant growth in Fe deficiency. At the same time, it increased the activities of superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) to protect the plasmolemma from peroxidation. Results demonstrated that different combinations of SNP and SA application could alleviate the chlorosis of peanut in Fe deficiency by various mechanisms. Such as increased the available Fe and chlorophyll concentrations in leaves, improved the activities of antioxidant enzymes and modulated the mineral elements balance and so on. Foliar application of SNP and SA is the best to protect leaves while directly adding them into nutrient solution is the best to protect roots. These results also indicated that the effects of SNP and SA supplying together to leaves or roots are better than respectively adding to roots and spraying to leaves. The best combination is foliar application of SNP and SA.